Status of neurocognitive and oxidative stress conditions in iron–steel workers - Malekirad, Ali Akbar; Mirabdollahi, Mansuoreh; Pilehvarian, Ali Asghar; Nassajpour, Ali Reza; Abdollahi, Mohammad (Toxicology and industrial health, 2015)
The aim of this study was to determine oxidative stress status as well as ferrous (Fe) and Copper (Cu) levels in blood, neurocognitive impairment, and clinical markers in iron–steel workers. A comparative cross-sectional analysis was performed in 50 iron–steel workers who have been in contact with Fe and Cu in comparison with a control group containing 50 healthy subjects in the same age group and sex. Blood levels of lipid peroxidation, total antioxidant capacity, Fe, and Cu along with neurocognitive impairment were measured in workers and controls. Clinical examination was accomplished to record any abnormal sign or symptoms. Comparing with controls, the workers showed higher blood levels of lipid peroxidation and Cu and also a lower total antioxidant capacity. There was a positive correlation between work history and interstitial lung disease that strengths the presumption to progress to chronic obstructive lung disease in future. The results indicate that exposure to a combination of Fe and Cu in iron–steel workers induces oxidative stress. Especially, in the present case, toxic effect of Cu has been more than positive effects of Fe, but the combined exposure resulted in no such critical toxicity.